Time of store effect on the structure and photophysical properties of the heated fat of the plant - Sulaiman, Luay Hamid; Shafeeq, Omar Shakir; Abbas, Nawras M.; Ali, Mays K.; Abd, Asraa K.; Chiad, Bahaa T.; Essa, Mohammed Shalan; Hamad, Mohammed Abdulla (Iraqi Journal of Science, 2019)
Vegetable sold oils (fat of the plant) were studied spectroscopy to determine its properties when it heating more than once, in this study the number of heating was 20 times and show the fat of the plant has been greatly affected by the heat. Aluminum and stainless steel were adopted for heating purposes. It turns out that the quality of the heating pot affects the spectrum specification. Changing the registered spectrum specifications for vegetable fat means a change in the characteristics of the same substance, which makes cooking use a second time with risks. Results were re-examined after six months showing significant risk of storage after heating to 300 oC the study proved that the structure of heating the vegetable oils changes and thus become edible cooking oil is not healthy and may be have toxic effects.